SISTEM INFORMASI PENGADUAN MAHASISWA POLITEKNIK BAJA TEGAL BERBASIS WEB - Dian Pramadhana (Lembaga Pengembangan Kinerja Dosen, 2022)
Information technology is one thing that has an important role in the current era, especially during the pandemic. Complaints or submission of aspirations and student complaints are important in an institution or college, because with the delivery of these aspirations a university can easily improve and improve its quality. Building student confidence in the services and facilities and infrastructure carried out by the organizers is an activity that must be carried out with the expectations and demands of students regarding service improvement. This student complaint system is a website-based system that is useful for assisting Tegal Steel Polytechnic students in submitting complaints to universities. Services regarding receiving complaints and responding to complaints are still manual. Students must come to the secretariat to fill out the form directly. Therefore, with the development of technology, it encourages authors to create a website-based information system that can help students who want to make complaints. Therefore, researchers build a website-based system that makes it easier for students to make complaints and see how far their complaints have been processed by the university.